Genome‐wide analysis of FOXO3 mediated transcription regulation through RNA polymerase II profiling. Issue 1 (22nd January 2013) - Eijkelenboom, Astrid; Mokry, Michal; de Wit, Elzo; Smits, Lydia M; Polderman, Paulien E; van Triest, Miranda H; van Boxtel, Ruben; Schulze, Almut; de Laat, Wouter; Cuppen, Edwin; Burgering, Boudewijn M T
<x xml:space="preserve">Abstract</x> Forkhead box O (FOXO) transcription factors are key players in diverse cellular processes affecting tumorigenesis, stem cell maintenance and lifespan. To gain insight into the mechanisms of FOXO‐regulated target gene expression, we studied genome‐wide effects of FOXO3 activation. Profiling RNA polymerase II changes shows that FOXO3 regulates gene expression through transcription initiation. Correlative analysis of FOXO3 and RNA polymerase II ChIP‐seq profiles demonstrates FOXO3 to act as a transcriptional activator. Furthermore, this analysis reveals a significant part of FOXO3 gene regulation proceeds through enhancer regions. FOXO3 binds to pre‐existing enhancers and further activates these enhancers as shown by changes in histone acetylation and RNA polymerase II recruitment. In addition, FOXO3‐mediated enhancer activation correlates with regulation of adjacent genes and pre‐existence of chromatin loops between FOXO3 bound enhancers and target genes. Combined, our data elucidate how FOXOs regulate gene transcription and provide insight into mechanisms by which FOXOs can induce different gene expression programs depending on chromatin architecture.